1999
DOI: 10.1021/jf990095s
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Group Modifications of the N-(Isothiazol-5-yl)phenylacetamides. Synthesis and Insecticidal Activity

Abstract: It has been shown that oxidation at the alpha-carbon of N-(4-chloro-3-methyl-5-isothiazolyl)-2-[p-[(alpha,alpha, alpha-trifluoro-p-tolyl)oxy]phenyl]acetamide (1) is conveniently brought about using dimethylformamide dimethylacetal to give N-(4-chloro-3-methyl-5-isothiazolyl)-beta-(dimethylamino)-p-[(alpha, alpha,alpha-trifluoro-p-tolyl)oxy]atropamide (2), which has served as a common starting point for a variety of functional group transformations. These transformations were found to proceed in moderate to goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…[18] Kinetics and mechanism for the reactions of N-methyl-N-phenylcarbamoyl chlorides with benzylamines in acetonitrile were reported by Koh et al [19] Matyk et al [20] reported the synthesis of a series of 64 derivatives of substituted heterocyclic analogues of salicylanilides, and the compounds were evaluated for in vitro antimycobacterial activity against Mycobacterium tuberculosis, M. avium and two strains of M. kansasii. Methylene group modifications of the N-(isothiazol-5-yl)phenylacetamides synthesis and insecticidal activity were reported by Samaritoni et al [21] Several works have reported on the antimycobacterial benzylsalicylamides, [22,23] and the activity of isoesters of salicylanilides: 2-sulfanylbenzanilides, N-benzylsulfanylbenzamides 3-hydroxy picolinanilides, N-benzyl-3-hydroxypicolinamides. [24] Vibrational spectroscopic study of acetate group was reported by Ibrahim and Koglin.…”
Section: Introductionmentioning
confidence: 92%
“…[18] Kinetics and mechanism for the reactions of N-methyl-N-phenylcarbamoyl chlorides with benzylamines in acetonitrile were reported by Koh et al [19] Matyk et al [20] reported the synthesis of a series of 64 derivatives of substituted heterocyclic analogues of salicylanilides, and the compounds were evaluated for in vitro antimycobacterial activity against Mycobacterium tuberculosis, M. avium and two strains of M. kansasii. Methylene group modifications of the N-(isothiazol-5-yl)phenylacetamides synthesis and insecticidal activity were reported by Samaritoni et al [21] Several works have reported on the antimycobacterial benzylsalicylamides, [22,23] and the activity of isoesters of salicylanilides: 2-sulfanylbenzanilides, N-benzylsulfanylbenzamides 3-hydroxy picolinanilides, N-benzyl-3-hydroxypicolinamides. [24] Vibrational spectroscopic study of acetate group was reported by Ibrahim and Koglin.…”
Section: Introductionmentioning
confidence: 92%
“…Arslan et al [11] reported the molecular structure and vibrational spectra of 2-chloro-N-(diethylcarbamothioyl)benzamide by Hartree-Fock (HF) and density functional methods. Methylene group modifications of the N-(isothiazol-5-yl)phenylacetamides synthesis and insecticidal activity are reported by Samaritoni et al [12] A vibrational spectroscopic study of acetate group is reported by Ibrahim and Koglin. [13] The assessment of the solid-state composition of an active salicylanilide compound by FT-Raman spectroscopy is reported by De Spiegeleer et al [14] The anion-triggered substituent-dependent conformational switching of salicylanilides was reported by Guo et al [15] .…”
Section: Introductionmentioning
confidence: 99%
“…fenpyroximate (Nihon Nohyaku 1991), pyridaben (Nissan 1991), fenazaquin (Dow 1993), tebufenpyrad (Mitsubishi 1993, Figure 7), pyrimidifen (Sankyo, Ube 1995, Figure 7). Much effort has also been devoted to the synthesis of insecticidal complex I inhibitors, and several interesting experimental products have been published such as OMI-88 from Mitsubishi or the isothiazolyl-phenylacetamides from DowAgro (Figure 8; Samaritoni et al,1999). However, toxicological problems with respect to mammals and fish, which compared to acaricides seem to be impossible to overcome in the case of insecticides, mean that no complex I inhibitor developed for pest insect control has yet been introduced to the insecticide market.…”
Section: Complex I Inhibitorsmentioning
confidence: 99%